English and Welsh teachers' perceptions of mindfulness in schools: modalities of implementing mindfulness in schools - Brito Pastrana, Rodrigo (2024)
To date, most of the research on Mindfulness-Based Interventions (MBIs) in schools in the UK context and worldwide has focused on the benefits of short and standardised mindfulness programmes for pupils and teachers from a positivist and quantitative perspective. Thus, many studies have reported cognitive, emotional and academic improvements in pupils and general wellbeing enhancement in teachers. However, in light of the increasingly critical literature within the field, it is possible to observe that a more profound and complex approach is needed. This study explores how these instrumental implementations are perceived by teachers from England and Wales with different degrees of expertise in teaching mindfulness. This qualitative study was informed by an itinerant rather than an iterative form of the action research cyclical model. Also, an onto-epistemological approach to observing and explaining data is adopted, informed by a phenomenological-hermeneutical philosophical perspective from which meaning is understood as a combination of teachers' voices and my own interpretations and reflections. After an initial literature review and the design of some interview questions (cycle one), data collection was realised in two stages, (cycles two and three) through interviews and focus groups. These explored participants' perspectives concerning current, generally more instrumental, implementations of mindfulness in schools, and more integral alternatives, respectively. The main findings show remarkable limitations of the instrumental approach and suggest the potentiality of implementing mindfulness more integrally, i.e., including cognitive, emotional, somatic, relational and spiritual dimensions alongside educational, philosophical, ethical and societal implications. These findings offer insights to inspire more integral and transformative ways of implementing mindfulness in schools. As a conclusion and vision for the future (cycle four), two significant and novel ideas worthy of emphasis are: (1) Integral and transformative implementations of mindfulness in schools should have educational rather than therapeutic purposes; (2) The fragile task of implementing mindfulness from a whole-school approach implies a systemic and evolving process, patiently and persistently permeating all sub-systems and levels of the school, starting with adults first. Thus, researchers in this field are challenged to develop more creative, complex and phenomenologically respectful approaches to teaching and researching mindfulness.